B98. Control of Ventilation: Wakefulness to Sleep, Animals to Humans 2009
DOI: 10.1164/ajrccm-conference.2009.179.1_meetingabstracts.a3692
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnea and Pain Share Affect-Related Brain Network.

Abstract: RATIONALE: Dyspnea and pain are similarly unpleasant sensations that share many characteristics which presumably include similar brain processing. Compared to pain, however, only little is known about the brain processes underlaying dyspnea. Therefore, study 1 examined whether dyspnea and pain are processed by common brain areas by using functional magnetic resonance imaging (fMRI), which was complemented by study 2 using a brain lesion approach. METHODS: In study 1, 14 healthy controls underwent conditions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Preliminary results suggest that tinnitus intensity may be related to auditory cortex activation (van der Loo 2009), but that the distress associated with its perception may be related to activation of a common general non-specifi c " distress network " . This notion is supported by recent studies which demonstrate activation of this network during distress related to dyspnoea (von Leupoldt et al 2009) and during unpleasant symptoms in a somatoform disorder, even in the absence of a real physical stimulus (Landgrebe et al 2008). Similar involvement of this " distress network " has been described in patients with depressive disorders (Drevets et al 2008).…”
Section: Neurobiology Of Tinnitus and Depressionsupporting
confidence: 57%
“…Preliminary results suggest that tinnitus intensity may be related to auditory cortex activation (van der Loo 2009), but that the distress associated with its perception may be related to activation of a common general non-specifi c " distress network " . This notion is supported by recent studies which demonstrate activation of this network during distress related to dyspnoea (von Leupoldt et al 2009) and during unpleasant symptoms in a somatoform disorder, even in the absence of a real physical stimulus (Landgrebe et al 2008). Similar involvement of this " distress network " has been described in patients with depressive disorders (Drevets et al 2008).…”
Section: Neurobiology Of Tinnitus and Depressionsupporting
confidence: 57%
“…mortality (depression is associated with almost doubled mortality over 1 year [30]) [52,53], a 10% increase in hospitalizations and diminished social and physical functioning (anxiety and depression are associated with a 13.7 point difference on the impact scale of the St George's Respiratory Questionnaire, on which 4 points is the minimally clinically important difference [54]) [23]. Furthermore, neuroimaging studies of breathlessness perception have identified activity in brain areas regularly associated with emotion and affective processing including the anterior cingulate cortex, insula and amygdala, as well as sensory processing areas [15,16,37,[55][56][57][58][59]. In healthy participants, anxiety sensitivity (defined as anxiety towards bodily sensations) appears to be related to individual variability in breathlessness perceptions, and also to brain activity in the precuneus during both the anticipation and perception of breathlessness, the anterior insula during mild breathlessness and parietal sensorimotor areas during strong breathlessness [60].…”
Section: Affectmentioning
confidence: 99%
“…The experience of a symptom entails a sensory-perceptual component referring to intensity, location, and other qualities, and an affective-motivational component providing the drive for action to preserve the integrity of the body [73][74][75][76][77]. A question prompting a symptom report from the individual requires an intuitive integration of both components into one global symptom report.…”
Section: Understanding Individual Differences In Symptom Overreportingmentioning
confidence: 99%